Fluid Field and Temperature Field Analysis of High Speed Magnetic Field Modulated Gears - Cheng Wenjie; Lu Huize; Xiao Ling; Li Ming (Jixie chuandong)
When a high speed magnetic field modulated gear is working, eddy current loss and wind friction loss will occur in permanent magnet and magnet block. In order to study the flow field and temperature field in small gaps of high speed magnetic gears, a magnetic gear with internal rotor speed of 16 500 r/min and external rotor speed of -3 000 r/min is taken as the research object. For the small gap of a magnetic gear, the flow field and temperature field calculation is carried out using computational fluid dynamics. It takes into account both natural convection and forced air cooling heat transfer. The results show that only by natural convection heat transfer, the permanent magnet will lose magnetism due to high temperature. When forced air cooling is introduced, the temperature of permanent magnet can be controlled within 402.98 K（129.83 ℃）. The convective heat transfer coefficient curve along the axial distribution is given when the axial wind speed is 15～30 m/s. The research results provide reference for thermal design of magnetic field modulated gears.